Nairobi Early Childcare in Slums (NECS) Study Protocol: a mixed-methods exploration of paid early childcare in Mukuru slum, Nairobi - Sunil Bhopal; Zelee Hill; Elizabeth W Kimani-Murage; Robert C Hughes; Patricia Kitsao-Wekulo; Betty R Kirkwood (BMJ Publishing Group, 2020)
Introduction The early years are critical. Early nurturing care can lay the foundation for human capital accumulation with lifelong benefits. Conversely, early adversity undermines brain development, learning and future earning.Slums are among the most challenging places to spend those early years and are difficult places to care for a child. Shifting family and work structures mean that paid, largely informal, childcare seems to be becoming the 'new normal' for many preschool children growing up in rapidly urbanising Africa. However, little is known about the quality of this childcare.Aims To build a rigorous understanding what childcare strategies are used and why in a typical Nairobi slum, with a particular focus on provision and quality of paid childcare. Through this, to inform evaluation of quality and design and implementation of interventions with the potential to reach some of the most vulnerable children at the most critical time in the life course.Methods and analysis Mixed methods will be employed. Qualitative research (in-depth interviews and focus group discussions) with parents/carers will explore need for and decision-making about childcare. A household survey (of 480 households) will estimate the use of different childcare strategies by parents/carers and associated parent/carer characteristics. Subsequently, childcare providers will be mapped and surveyed to document and assess quality of current paid childcare. Semistructured observations will augment self-reported quality with observable characteristics/practices. Finally, in-depth interviews and focus group discussions with childcare providers will explore their behaviours and motivations. Qualitative data will be analysed through thematic analysis and triangulation across methods. Quantitative and spatial data will be analysed through epidemiological methods (random effects regression modelling and spatial statistics).Ethics and dissemination Ethical approval has been granted in the UK and Kenya. Findings will be disseminated through journal publications, community and government stakeholder workshops, policy briefs and social media content.